2009
DOI: 10.1007/s10339-009-0337-0
|View full text |Cite
|
Sign up to set email alerts
|

Good judgments do not require complex cognition

Abstract: What cognitive capabilities allow Homo sapiens to successfully bet on the stock market, to catch balls in baseball games, to accurately predict the outcomes of political elections, or to correctly decide whether a patient needs to be allocated to the coronary care unit? It is a widespread belief in psychology and beyond that complex judgment tasks require complex solutions. Countering this common intuition, in this article, we argue that in an uncertain world actually the opposite is true: Humans do not need c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 129 publications
0
111
0
3
Order By: Relevance
“…This repertoire forms an "adaptive toolbox" of heuristics, each of which exploits how basic cognitive capacities, such as memory, represent regularities in the structure of our environment. In doing so, heuristics can yield accurate judgments by operating on little information-say, a sense of recognition (for a recent overview, see Marewski, Gaissmaier, & Gigerenzer, 2010).…”
Section: Strategy Selection By Default?mentioning
confidence: 99%
“…This repertoire forms an "adaptive toolbox" of heuristics, each of which exploits how basic cognitive capacities, such as memory, represent regularities in the structure of our environment. In doing so, heuristics can yield accurate judgments by operating on little information-say, a sense of recognition (for a recent overview, see Marewski, Gaissmaier, & Gigerenzer, 2010).…”
Section: Strategy Selection By Default?mentioning
confidence: 99%
“…By extension this may lead to the assumption that high experientiality will be negatively associated with diagnostic reasoning and would then be related to lower diagnostic classification accuracy. On the other hand, it has been suggested that good judgments do not always require complex cognition and that heuristic processing can sometimes outperform complex cognitive processing (Gigerenzer and Gaissmaier 2011;Marewski et al 2010). Rapid heuristic, experiential thinking would then, again maybe counter-intuitively, lead to higher diagnostic accuracy.…”
mentioning
confidence: 99%
“…The traditional process requires systematic series of drawings and sketches that follow through with the lecturers' supervision and consent. This process is in contrast with current situation whereby ideas are rather seen to be captured through heuristic thinking [10], divergent thinking or influences from other sources of design on the internet when students sit behind their computers in their quest for solutions in design. The situation has generated some controversy pedagogically, especially with ideation in the digital domain.…”
Section: Problem Statementmentioning
confidence: 86%